Work–Life Balance as a Mediator in an Islamic Context: Burnout, Career, and Satisfaction - Hanuna Shafariah; Abdul Gofur (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2026)
This study investigates how burnout and career development influence job satisfaction via work–life balance among Muslim employees in Jakarta, integrating Islamic management principles. Using structural equation modelling, results indicate burnout negatively impacts work–life balance, while career development directly enhances job satisfaction. Crucially, work–life balance mediates the relationship between burnout and satisfaction. However, career development showed no significant link to work–life balance. The study uniquely combines behavioral theory with Islamic perspectives, highlighting that minimizing emotional strain is essential for maintaining the balance required for employee well-being.